ISOLASI DAN IDENTIFIKASI RIMPANG TEMULAWAK (Curcuma xanthorrohza Roxb.) DAN BUNGA LAVENDER (Lavandula angustifolia Mill.) - rani prabandari; desy Nawangsari; Kukuh Yunianto Sumargo (Viva Medika, 2019)
Essential oils are fragrance agents in plants. Essential oils have a volatile component in some plants with certain characteristics. At present, essential oils have been used as perfume, cosmetics, food additives and medicine. Empiric ethnopharmacology studies on aromatherapy plants show that Indonesia has 49 types of aromatic plants from 22 types of tribes, 12 of which are empirically used as aromatherapy with calming and refreshing effects (Sangat 1996 in Rahmawati, 2010). One example of aromatherapy used is the ginger rhizome (Curcuma xanthorrihza Roxb) and Lavender Flower (Lavandula angustifolia Mill.). This study aims to isolate and identify the essential oils of Temulawak rhizome (Curcuma xanthorrihza Roxb) and Lavender Flowers (Lavandula angustifolia Mill.). The essential oil isolation step uses the Steam Water Distillation method, after which the essential oil obtained is identified to ensure its purity. The results showed that Temulawak essential oil and Lavender essential oil were carried out using the water distillation method, obtained levels of 2.3% and 1.8%. Essential oils in Temulawak were identified by testing their physical properties which include specific gravity, solubility in ethanol 90%, solubility in chloroform and oil in NaCl. The identification results obtained in the Temulawak rhizome and Lavender plants are specific gravity 0.9436 and 0.8221. Solubility in ethanol 90% with a volume ratio of 1: 3.7 mL and 1: 3.3 mL. solubility in chloroform of 1: 3.3 mL and 1: 3.3 mL. on the addition of NaCl in the oil oil reduction occurs.